Kebersihan Gigi Tiruan pada Lansia, Suatu Tinjauan Metode dan Bahan - Kartika Indah Sari; Warta Dewi; Tadeus Arufan Jasrin; Taufik Sumarsongko (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2018)
The use of removable dentures is one of the main approach to oral rehabilitation of partially or completely edentulous patient. Denture hygiene is an important things for the elderly as a vulnerable people. The purpose is to discribe both of the literature or recent study that related to denture hygiene in elderly. Removable denture got special attention cause accumulate food residue, bacterial biofilm, and calculus at the mucosa or denture interface. Recently, the presence of bacterial bioflim on denture was considered a risk factor for aspiration pneumonia in frail older people. In general, removable denture that is used acrylic based denture.The microporous surfaces of an acrylic denture provide a wide range of environments to support microorganisms that can threaten the health of patient. Knowing denture cleanser as apart of denture hygiene in elderly is an important things.